1992
DOI: 10.3171/jns.1992.76.1.0072
|View full text |Cite
|
Sign up to set email alerts
|

Chemical monitoring of neurosurgical intensive care patients using intracerebral microdialysis

Abstract: The authors have used intracerebral microdialysis to develop a method for routine monitoring of disturbances in brain energy metabolism in patients in the neurosurgical intensive care unit. Microdialysis was conducted for periods ranging from 2.3 to 8.3 days in four patients (three with severe head injuries and one with severe subarachnoid hemorrhage). Altogether, 4447 chemical analyses from 587 dialysis samples were carried out. Concentrations of the energy-related metabolites lactate, pyruvate, and hypoxanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
1
11

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(177 citation statements)
references
References 37 publications
10
155
1
11
Order By: Relevance
“…Clinically, a multitude of studies have detected significant increases in extracellular glutamate levels in the days following injury, with some reports correlating increases in extracellular glutamate with unfavorable outcomes (Bullock et al, 1995Chamoun et al, 2010;Hlatky et al, 2004;Hutchinson et al, 2002;Koura et al, 1998;Persson and Hillered 1992;Reinert et al, 2000;Timofeev et al, 2011;Vespa et al, 1998;Yamamoto et al, 1999). These studies emphasize the significance of glutamate dysregulation in the acute pathophysiology and consequences of TBI.…”
Section: Introductionmentioning
confidence: 94%
“…Clinically, a multitude of studies have detected significant increases in extracellular glutamate levels in the days following injury, with some reports correlating increases in extracellular glutamate with unfavorable outcomes (Bullock et al, 1995Chamoun et al, 2010;Hlatky et al, 2004;Hutchinson et al, 2002;Koura et al, 1998;Persson and Hillered 1992;Reinert et al, 2000;Timofeev et al, 2011;Vespa et al, 1998;Yamamoto et al, 1999). These studies emphasize the significance of glutamate dysregulation in the acute pathophysiology and consequences of TBI.…”
Section: Introductionmentioning
confidence: 94%
“…The ratio of lactate to pyruvate has been one of the commonly reported features of microdialysis monitoring since proposed by Hillered (Persson and Hillered, 1992;Valtysson et al, 1998). LPR ratio normally ranges o20 under conditions of uncomplicated metabolism.…”
Section: Lpr As a Marker Of Metabolic Crisismentioning
confidence: 99%
“…Clinical studies have shown critically reduced cerebral blood flow [4] following head injury and the presence of ischemia at the tissue level has been further demonstrated in studies where local brain tissue pO2 [20] or jugular oxygen saturation [21] was continuously monitored or microdialysis [17] performed. Although debate exists over the causes of low CBF after head injury, the consequences of secondary ischemic damage are evident, and the adverse influence of further systemic hypoxic and hypotensive insults has been well documented [6,8,14].…”
Section: Early Management Of Head Injurymentioning
confidence: 99%